2021
DOI: 10.23910/1.2021.2272
|View full text |Cite
|
Sign up to set email alerts
|

Agro-techniques for Production of Seed Size Tubers in Conventional Seed Potato Production System–A Review

Abstract: The seed potato cost is very important component in total potato production and account for 30 to 70% which varies depending on the country or region. Tuber size is an important factor to decide the seed requirement per unit area. Seed size affects total yield, graded or marketable tuber yields. Standard seed tuber of 25–125 g weight (30–55 mm) is known as seed size tubers in India. Obtaining seed size tuber is important for achieving higher potential of the cultivars. The tuber size profile can be reduced or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…(670 thousand/ha) over the other three varieties [22]. Also supported by Sadawarti et al [30] who noted that the mean total tuber number found maximum in the variety Kufri Sindhuri (648 thou/ha) over Kufri Chandramukhi and Kufri Chipsona-1 when planted under west-central Indian condition this for seed production. Similar variations among different genotypes were also recorded in current findings.…”
Section: Marketable Tuber (>20g) Yield (T/ha)mentioning
confidence: 60%
“…(670 thousand/ha) over the other three varieties [22]. Also supported by Sadawarti et al [30] who noted that the mean total tuber number found maximum in the variety Kufri Sindhuri (648 thou/ha) over Kufri Chandramukhi and Kufri Chipsona-1 when planted under west-central Indian condition this for seed production. Similar variations among different genotypes were also recorded in current findings.…”
Section: Marketable Tuber (>20g) Yield (T/ha)mentioning
confidence: 60%
“…Potato crop needs to get enough intra and inter row spacing to allow maximum inititation of number of stems / plant as well as an optimum number and better quality tuber formation. The optimizing of plant density is one of the most important subjects of potato production management because it affects seed cost, plant development, yield, and quality of the crop (Bussan et al, 2007, Sadawarti et al, 2021b). An ideal combination of plant population, row width, and in-row seed spacing for a particular variety were the major factors for optimizing tuber size (Rex and Mazza, 1989).…”
Section: Plant Population/spacingmentioning
confidence: 99%
“…Sustainable potato production depends on constant renewed supply of disease-free planting material, improving quality seed production and seed distribution. Under potato, cultivation, seed is the highest cost-bearing input accounting for 40-50% of the total cost of its cultivation (Venkataslam et al, 2011, Sadawarti et al, 2021aBuckseth et al, 2022). Poor seed quality, lack of availability, limited access to high-quality seed, lack of access to preferred and adapted varieties, and inefficient seed systems is the major problem in higher productivity in potato (Anonymous, 2016;Singh et al, 2016;Bentley et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A study by M.J. Sadawarti et al (2021) established the effect of seed tuber size on the overall yield and output of commercial tubers. In the paper of S. Ebrahim et al (2018), a research on the effect of seed tuber size (fractions 25-54, 35-45, and 46-55 mm) on the productivity of three potato varieties Gudenie, Jalene, and Kellacho in Ethiopia is presented.…”
Section: Introductionmentioning
confidence: 99%